The profile of students' mathematical representation competence, self-confidence, and habits of mind through problem-based learning models - Ahmad Ahmad; Lukmanul Akhsani; Zulkifley Mohamed (Jurnal Infinity, 2023)
Mathematics is an essential subject for students. Teachers, therefore, need to provide innovative learning that develops students' mathematical skills. This study was conducted to determine the effect of a problem-based learning (PBL) model on students' mathematical representation competencies, self-confidence, and habits of mind. It used a quantitative methodology and was conducted on eighth-grade students divided into an experimental class with a PBL model and a control class with a direct learning model. The results showed that the mathematical representation competencies of the students in the experimental class were better than those in the control class. Students' self-confidence and habits of mind also influenced their mathematical representation competencies. It shows that the PBL model positively affects students' mathematical representation competency, self-confidence, and habits of mind. Teachers can use the PBL model to develop their students' mathematical representation competencies by paying attention to students' self-confidence and habits of mind.